THU0586 Ankylosing Spondylitis (AS) Self-Management Education Program – 6 Month Follow-Up Results. (9th June 2015) - Inderjeeth, C.A.; Raymond, W.; Connor, C.; Edelman, J.; Cook, N.; Briffa, K.; McQuade, J.
Abstract : Background: Disease specific self-management interventions are rare. After a needs assessment, focus group discussions, and Plan, Do, Study, Act (PDSA) model we developed and tested the Self Management for Ankylosing Spondylitis (SMAS) program, for people with Ankylosing Spondylitis (AS). Objectives: To examine the benefits of an SMSA program for people with AS regarding change in health status, quality of life, and disease activity. Methods: 134 people were recruited in this case cohort intervention. Exclusion criteria: <18yo; non-English speaking; co-morbid inflammatory musculoskeletal disease; and/or visual, auditory, or cognitive impairment. Participants attended a weekly 2.5 hour self-management education session facilitated by same two health professionals over 6 weeks. The scripted content included multidimensional strategies including stretches; and optional 7th week supervised exercise class. Demographic, AS disease management characteristics, medication patterns, and outcomes were measured at baseline, 6 weeks, 3 and 6 months using repeated measures ANOVA for: back pain (VAS), fatigue (MAF), anxiety and depression (HAD), health distress (HDq), fatigue severity scale (FSS), pain self-efficacy (PSEQ), quality of life (SF-36) and Evaluating Ankylosing Spondylitis Qol (EASIQol), global perceived health (GPH), patients disease global assessment (PDGA). AS outcomes were analysed using repeated measures ANOVA for: Bath Ankylosing Spondylitis – Global, Disease Activity Index, and Functional Index (BAS-G, BASDAI, & BASFI), and Ankylosing Spondylitis QoL (ASQol). Results: At baseline, 43.3% were male, and the mean age was 47.2±15.1 years. The median time to AS diagnosis from the index symptom experience was 3 years with an IQR (1-6). The BAS-G improved between baseline and 3 months (p=0.011) and were sustained at 6 months (p=0.039). The BASDAI improved between baseline and 3 months (p=0.01) and were sustained at 6 months (p=0.009). The ASQol improved between baseline and 6 months (p=0.051). A positive trend were seen for the MAFs GFI, back pain (i.e. nocturnal and total), and the PDGA over the 6 months although these trends were not statistically significant. The composite SF-36 (physical and mental), HADs, HDq, FSS, composite Easiqol (physical, disease activity, wellbeing, and social), PSEQ demonstrated no improvement over the study. There was no significant change in medication usage over the 6 months. Conclusions: SMAS for AS is independently effective in improving AS specific Disease activity, but global QOL scores did not change. References: Von Korff M, Glasgow RE, Sharpe M. Organising care for chronic illness. BMJ 2002;325:92-94. Zochling J. Measures of symptoms and disease status in ankylosing spondylitis. Arthritis Care Res 2011;63:S47-S58. Disclosure of Interest: None declared